Vaccines as a Preventive Modality for Malaria: A Review - Lewis, Shaila A. (Asian Journal of Pharmaceutics (AJP), 2018)
Malaria is one among the several parasitic infections that continue to claim lives despite the tremendous progress in the techniques for diagnosis, prevention, and treatment. Although the figures of malaria-ridden patients are decreasing in all the countries due to the collective efforts from all sectors of the society, the tropical countries are still facing severe setbacks in the implementation of the health measures due to the emergence of resistant strains and non-availability of appropriate medications at the required time. An efficient strategy would be to develop vaccines to prevent malaria from occurring than treating it. This review reflects the significant progress made in the field of vaccines and the challenges associated with it. A comprehensive summary is provided for the various diagnostic tests available for detecting malaria and the aspects of treatment related to infections during pregnancy.